Vİews Of The Teachers And Administrators Of The High School Of Fine Arts And Sports On Diversity Management, - Karademir, T., Çoban, B., Devecioğlu, S., Karakaya, Y. E., Yücel, A. S., (My University, 2012)
This study was conducted for the purpose of determining the views on management of diversity of the administrators and the teachers who work in Fine Arts and Sports High Schools. The sample group of the study consisted of 12 administrators and 70 teachers working in the fine Arts and Sports High Schools in province of Elazig, Usak, Trabzon, Corum and Eskisehir. In order to determine the views of the sample group, a scale developed by Balay and Saglam (2004) was used and the data obtained was analyzed in the SPSS package program. In this study it was determined that managers didn’t discriminate according to sexes, that there was a decrease in views of the managers and teachers that personal attitudes and behaviors and the administrative practices and principles were managed positively with their growing ages and that there was no difference in views of the study group regarding the diversity management in their schools according to their education status, vocational superiority, total service periods in management, service status and vocational field variants. In conclusion, it can be concluded that the differences between the administrators and the teachers in these educational institutions have a positive impact on the direction of improving the quality of education and that the employees’ beliefs, origins, cultural, etc. differences provide an advantage for these institutions and finally there were no discrimination in their administrative concepts.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Management; Diversity; Diversity Management; Sports High Schools